Irrigation development and equity implications: the case of India. Issue 3 (4th May 2022) - Kuriachen, Philip; Suresh, A.; Aditya, K. S.; Venkatesh, P.; Sen, Biswajit; Yeligar, Sharath S.
ABSTRACT: This paper examines the inequity in irrigation distribution in India using a variant of Theil's entropy measure for the period 1995–2010. The analysis reveals that the level of inequity in irrigation distribution has increased over time. Inequity has declined in canal, tank and well-irrigated systems and increased in the tube well-irrigated system. Decomposition analysis revealed that regional disparities have declined in all sources of irrigation except for tube wells. The role of property rights to groundwater, groundwater markets, energy pricing policy and competitive deepening of wells in worsening the inequity in access to groundwater resources is also discussed.